Rheumatology Quiz (Eng) - Suesuwan, Anawat (Thai Journal of Rheumatology, 2025)
A 34-year-old woman presented with a bruise around the right medial malleolus (Figure 1). She felt mild pain and swelling in her knee for the past ten days and noticed the bruise two days ago. Questions: 1. What is her clinical sign? 2. What is her diagnosis?